Experimental study on the use of aluminum waste as a heat energy storage medium in laboratory-scale drying equipment - Apriandi, Nanang; An-Nizhami, Avicenna; Herlambang, Yusuf Dewantoro; Raharjanti, Rani; Rachman, Iqo Yovie; Suseno, Sigit; Khoirunnisa, Hilma; Khusna, Atina Nurul (Universitas Muhammadiyah Mataram, 2024)
One of the best ways to reduce food loss during harvest is drying. The main challenge in the drying process is reducing energy consumption as a heat source in drying equipment. Integrating thermal energy storage (TES) into drying equipment has proven to be an effective way to enhance energy efficiency in the drying process. This research aims to explore the potential of TES material in the form of aluminium chips sourced from machining waste and integrated into a drying device. The thermal characteristics of the drying system without and with the addition of TES are compared and evaluated under two testing conditions, namely charging and discharging. The results show that the integration of TES in the drying system can reduce the percentage of temperature drop in the drying chamber due to the charging-discharging process by 58.57%, with the average percentage of temperature drop in the drying chamber without and with the addition of TES being 25.56% and 10.59%, respectively. Overall, aluminium chips obtained from machining waste can be used as an alternative TES material that is environmentally friendly, inexpensive, and readily available.